Education and the humanitarian space: is there a dissonance between military education and military practice in the Irish Defence Forces? - Connors, Niall (2018)
This thesis is centred on education and the humanitarian space, specifically, an analysis of whether there a dissonance between military education and military practice in the Irish Defence Forces. In this context, the research audience is considered to be constituted of two distinct cohorts; military personnel within the Irish Defence Forces and individuals within the development sector, in particular those with responsibility for the education and ‘pre-deployment’ training of those within the humanitarian space.